PENYULUHAN KESEHATAN TENTANG KELUARGA BERENCANA PADA WANITA USIA SUBUR DI DESA SUNGAI TUAN ULU KABUPATEN BANJAR KALIMANTAN SELATAN - Rusdiana; Hj. Zubaidah; Raihana Norfitri; Susanaria Alkai (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The family planning program is an attempt to regulate the arrangement, the number of children, and the birth spacing of children to create a quality family. The family planning program is also a strategy to reduce maternal mortality, especially with 4T mothers; Giving birth too young (under 20 years old), giving birth too often, giving birth too early, and giving birth too old (over 35 years old). The age couple in the village, even though they have participated in the family planning program, both contraceptives, pills and implants, in practice they also do not comply with the rules for using these contraceptives, especially the contraceptive pills consumed are not according to the type and the rules for use. This service activity aims to provide education about the use of contraceptives, especially for eligible women. The method used is health education. The target number of activities is 17 people of eligible women who visited the Posyandu in Sungai Tuan Ulu Village. Service activities include coordinating with village heads, coordinating with midwives and posyandu cadres, and conducting counseling at an early age. The results obtained are all respondents are able to understand about contraceptives.